BRIQUETAGEM DO RESÍDUO DO BAGAÇO DA CANA-DE-AÇÚCAR NUMA DESTILARIA DE AGUARDENTE - Werlang, Reimundo V.; Starlick, Gustavo A.; Santos, Luis H. P. d.; Picinin, Alexandre (Salão do Conhecimento, 2013)
Resumo